Sacrificial Worship (Qurban) Motivation Determinant Factors of Tuatunu Population in Pangkalpinang City - Hendra Cipta (Faculty of Islamic Economics and Business, State Islamic University Sunan Kalijaga, 2020)
This article intends to find an answer to the high level of community participation in Tuatunu Urban Village in the City of Pangkalpinang, Bangka Belitung Islands Province in the sacrificial worship (qurban) motivation during the Eid al-Adha feast day. Tuatunu Urban Village only has a population of approximately 9,000 inhabitants and the average livelihood of its inhabitants is as pepper, rubber, and pineapple farmer. But in Eid al-Adha 2019, the level of participation of the people who follow the sacrificial worship from the five mosques in this area is highest when compared to the seven sub-districts in the Municipality of Pangkalpinang. Tuatunu Urban Village sacrifices approximately 32 cows at Eid al-Adha 2019, where seven people bear one cow. This urban village celebrates Eid al-Adha like Eid al-Fitr where residents visit each other's neighbors. This article is the result of quantitative research with the dependent variable is a sacrificial worship motivation and the independent variables are religiosity, generosity, avoid harm, and social status. This study found that the variables that influence the motivation to sacrificial worship the people of Tuatunu Urban Village are the factors of religiosity, social status, and avoid harm while the elements of generosity do not significantly influence the motivation to sacrifice.